Quantum model of naturally rotating Machian cosmology and galactic applications of current cosmic angular velocity - V.S. Seshavatharam, U.; Lakshminarayana, S. (International Journal of Advanced Astronomy, 2021)
We would like to emphasize that, extraordinary physical concepts like Big bang, Inflation, Dark energy and Superluminal expansion demand super-normal efforts and need observational support. Observational data is raising day-by-day non-conformity and demanding changes in the original concepts. It is very interesting to note that James Peebles, the famous cosmologist and 2019 Nobel laureate strongly believes that Big bang concept is inappropriate in understanding the universe. It is better to understand and develop models of cosmology based on well supported physical concepts rather than extraordinary physical hypothesis. Unification point of view, quantum cosmology must be given a priority and one should make a note that, Spin is a basic property of quantum physics and rotation is a very common experience. In this context, with reference to life cycle of living creatures and independent of red-shift data, we have developed a quantum model of cosmology associated with Machian universe having Planck scale origin, total dark matter, light speed expansion, light speed rotation, equality of gravitational self energy density and thermal energy density, radially decreasing internal acceleration and radially increasing anisotropy. We are working on understanding and correlating observed redshift data in a unified approach. In this letter, we present various galactic applications of current cosmic angular velocity.Â Â